2006
DOI: 10.1001/jama.296.10.1274
|View full text |Cite
|
Sign up to set email alerts
|

Does This Patient With Headache Have a Migraine or Need Neuroimaging?

Abstract: The presence of 4 simple historical features can accurately diagnose migraine. Several individual clinical features were found to be associated with a significant intracranial abnormality, and patients with these features should undergo neuroimaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 58 publications
2
64
0
4
Order By: Relevance
“…32 Headache with associated features. A recent review of the literature of headache with associated features 33 found the following relevant positive likelihood ratios (likelihood ratio = post probability/prior probability) with 95% confidence intervals (95% CIs): headache with abnormal findings on clinical neurological examination 5.3 (95% CI = 2.4 to 12); headache aggravated by exertion or Valsalva-like manoeuvre 2.3 (95% CI = 1.4 to 3.8); headache with vomiting 1.8 (95% CI = 1.2 to 2.6); headache with focal symptoms 3.1 (95% CI = 0.37 to 25); worsening headache 1.6 (95% CI = 0.23 to 10); and cluster headache 10.7 (95% CI = 2.2 to 52). Another review has given rapidly increasing headache frequency 12 (95% CI = 3 to 48); headache causing awakening from sleep 98 (95% CI = 10 to 960); and dizziness or lack of coordination 49 (95% CI = 3 to 710).…”
Section: What Clinical Symptoms or Signs Indicate A Particular Levelmentioning
confidence: 99%
“…32 Headache with associated features. A recent review of the literature of headache with associated features 33 found the following relevant positive likelihood ratios (likelihood ratio = post probability/prior probability) with 95% confidence intervals (95% CIs): headache with abnormal findings on clinical neurological examination 5.3 (95% CI = 2.4 to 12); headache aggravated by exertion or Valsalva-like manoeuvre 2.3 (95% CI = 1.4 to 3.8); headache with vomiting 1.8 (95% CI = 1.2 to 2.6); headache with focal symptoms 3.1 (95% CI = 0.37 to 25); worsening headache 1.6 (95% CI = 0.23 to 10); and cluster headache 10.7 (95% CI = 2.2 to 52). Another review has given rapidly increasing headache frequency 12 (95% CI = 3 to 48); headache causing awakening from sleep 98 (95% CI = 10 to 960); and dizziness or lack of coordination 49 (95% CI = 3 to 710).…”
Section: What Clinical Symptoms or Signs Indicate A Particular Levelmentioning
confidence: 99%
“…Evaluation for neurovascular compression with MRI has a reported high sensitivity and specificity [28 ,29].Headaches are another indication for advanced imaging. Headache may indicate the presence of tumors, aneurysms,orarteriovenous malformations depending on nature of theheadache [30].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Eine ausführliche und präzise Anamnese ist dabei unerlässlich und hilft unnötige apparative Abklärungen zu vermeiden [6]. …”
Section: Klinische Aspekte ((ü1))unclassified